2017
DOI: 10.1016/j.ijscr.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Ante situm liver resection with inferior vena cava replacement under hypothermic cardiopolmunary bypass for hepatoblastoma: Report of a case and review of the literature

Abstract: HighlightsHypothermic cardiopolmunary bypass is safe for prolonged total vascular exclusion.Ante situm liver resection is feasible for hepatoblastoma considered unresectable.Inferior vena cava replacement with aortic graft from cadaveric donor is feasible.Preoperative and intraoperative assessment are essential to achieve good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
(23 reference statements)
1
11
0
2
Order By: Relevance
“…Vascular reconstruction with extracorporeal circulation is a challenging surgical technique in hepatic resection or LT for HB with tumor thrombi extending into the IVC and RA. To the best of our knowledge, 16 cases of extracorporeal circulation for cases of HB with IVC thrombi or RA (including the present case) have been reported, as shown in Table 1 6,9,12,22‐26 . Hepatic resection was performed under cardiopulmonary bypass with hypothermic perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular reconstruction with extracorporeal circulation is a challenging surgical technique in hepatic resection or LT for HB with tumor thrombi extending into the IVC and RA. To the best of our knowledge, 16 cases of extracorporeal circulation for cases of HB with IVC thrombi or RA (including the present case) have been reported, as shown in Table 1 6,9,12,22‐26 . Hepatic resection was performed under cardiopulmonary bypass with hypothermic perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Papamichail et al described IVC reconstruction using cadaveric IVC graft without post-operative vascular complications [18]. For other hepatic tumours invading the IVC, aortic grafts from deceased donors were also adopted, with the possible advantage of reducing the risk of vessel collapse due to its thickness [40]. Moreover, cadaveric grafts have the possible advantage of not requiring long-term anticoagulation therapy [41].…”
Section: Figurementioning
confidence: 99%
“…The ante situm operation was first described in 1991 by Hannoun [52] (Figure 3B-D). This technique entails complete mobilisation of the liver and vena cava, TVE and HP through the PV, followed by sections of the hepatic veins or the vena cava itself [40]. This allows complete rotation of the liver (ex situ), giving full access to the posterior liver, cava and hepatocaval confluence, while preserving the hepatic pedicle (in vivo) and reducing the risk of vascular complication into the hilum vessels, especially to the hepatic artery.…”
Section: Figurementioning
confidence: 99%
“…Qiu et al indicated type IV end-stage HAE patients with the opportunity to be operated in vivo based on "IHP" vascular infiltrated degree classification (36). For some cases, ante-situm liver resection with inferior vena cava (IVC) replacement procedure replaced ERAT procedure for radical resection for some special location (28,37). And, the continuous pringle maneuver and in situ hypothermic perfusion through the inferior mesenteric vein (IMV) may resect the lesion in vivo, rather than removing the entire liver for lesion resection in vitro (38).…”
Section: Candidatementioning
confidence: 99%